2016
DOI: 10.1016/j.gene.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale metabolic modeling of Mucor circinelloides and comparative analysis with other oleaginous species

Abstract: We present a novel genome-scale metabolic model iWV1213 of Mucor circinelloides, which is an oleaginous fungus for industrial applications. The model contains 1213 genes, 1413 metabolites and 1326 metabolic reactions across different compartments. We demonstrate that iWV1213 is able to accurately predict the growth rates of M. circinelloides on various nutrient sources and culture conditions using Flux Balance Analysis and Phenotypic Phase Plane analysis. Comparative analysis of three oleaginous genome-scale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…Previous studies have presented GEMs of several oleaginous fungal species, including oleaginous ascomycete Yarrowia lipolytica (Loira, Dulermo, Nicaud, & Sherman, 2012), zygomycetes Mortierella alpina (Ye et al, 2015) and Mucor circinelloides (Vongsangnak et al, 2016). Our study presents the 355 first reconstruction of GEM of lipid-accumulating basidiomycete R. toruloides, and while we used the S. cerevisiae model as reference for the conserved parts of metabolism, rhto-GEM contains unique characteristics including ATP:citrate lyase, which is the main source of acetyl-CoA for lipid synthesis; mitochondrial beta-oxidation; a cytoplasmic malic enzyme that provides an alternative to the PP pathway for NADPH regeneration; and pathways related to poly-unsaturated fatty acids and carotenoid 360 biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have presented GEMs of several oleaginous fungal species, including oleaginous ascomycete Yarrowia lipolytica (Loira, Dulermo, Nicaud, & Sherman, 2012), zygomycetes Mortierella alpina (Ye et al, 2015) and Mucor circinelloides (Vongsangnak et al, 2016). Our study presents the 355 first reconstruction of GEM of lipid-accumulating basidiomycete R. toruloides, and while we used the S. cerevisiae model as reference for the conserved parts of metabolism, rhto-GEM contains unique characteristics including ATP:citrate lyase, which is the main source of acetyl-CoA for lipid synthesis; mitochondrial beta-oxidation; a cytoplasmic malic enzyme that provides an alternative to the PP pathway for NADPH regeneration; and pathways related to poly-unsaturated fatty acids and carotenoid 360 biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The compositions of amino acids and DNA were directly taken from the protein and DNA sequence information of M. circinelloides WJ11, respectively (Tang et al, 2015a). The compositions of lipids, carbohydrates and RNA were adopted from the published model of M. circinelloides reference strain CBS277.49 ( i WV1213) (Vongsangnak et al, 2016). For energetic parameters, ATP requirements for nongrowth associated purposes (mATP) and synthesis of biomass from macromolecules (K ATP ) and the operational P/O ratio were considered.…”
Section: Methodsmentioning
confidence: 99%
“…In oleaginous fungi, the reconstruction of the GEM of Mortierella alpina was implemented to investigate the metabolic characteristics for enhancing the production of lipids rich in arachidonic acid (Ye et al, 2015). Furthermore, Vongsangnak et al (2016) also demonstrated the empowering of GEM for dissecting the growth behavior of M. circinelloides strain CBS 277.49 on various nutrient sources through the comparative analysis of the three GEMs of M. circinelloides ( i WV1213), M. alpina ( i CY1106) (Ye et al, 2015) and Y. lipolytica ( i YL619_PCP) (Pan & Hua, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have presented GEMs of several oleaginous fungal species, including oleaginous ascomycete Yarrowia lipolytica (Loira, Dulermo, Nicaud, & Sherman, ), zygomycetes Mortierella alpina (Ye et al, ), and Mucor circinelloides (Vongsangnak et al, ). Our study presents the first reconstruction of GEM of lipid‐accumulating basidiomycete R. toruloides , and while we used the S. cerevisiae model as reference for the conserved parts of metabolism, rhto‐GEM contains unique characteristics including ATP:citrate lyase, which is the main source of acetyl‐CoA for lipid synthesis; mitochondrial β‐oxidation; a cytoplasmic malic enzyme that provides an alternative to the pentose phosphate pathway for NADPH regeneration; and pathways related to polyunsaturated fatty acids and carotenoid biosynthesis.…”
Section: Resultsmentioning
confidence: 99%